Pengaruh Motivasi, Gaya Hidup, Persepsi dan Pembelajaran terhadap Keputusan Pembelian Honda Pcx pada dealer Sumber Cahaya Motor Palembang: Pengaruh Motivasi, Gaya Hidup, Persepsi dan Pembelajaran terhadap Keputusan Pembelian Honda Pcx pada dealer Sumber Cahaya Motor Palembang - Tandi, james (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2023)
The purpose of this study is to analyze the motivational and lifestyle agents that influence the decision to purchase Honda pcx motorcycles at Sumber Cahaya Motors dealers. The data collection for this study distributed questionnaires to 102 respondents. The sampling uses nonprobability sampling using the purpsisve sampling method with the help of SPSS 24